The impact of Some Social – Economic Characteristics of Farmers on exposure to Different Agriculture Information Sources: A study in some Area of Al-Jabal Al-Akhdar Region, in Libya (Albayan Scientific Journal, 2023)
The main purpose of this study was to determine farmers exposure degree to different agriculture information sources,and the impact of some socio-economic characteristics on  120 farmers were selected by random sample, which representing  about 22%  of total population of farmers. The data were collected through personal interviews questionnaire. The data were analyzed by using many statistical techniques such as means, standard deviation, simple correlation coefficient, and multiple step –wise regression. The main findings of this study were:     About 54% of farmers have low exposure degree to the individual agriculture information source, while about 72% of them have medium and high exposure degree to group information sources. And nearly 55% of the farmers have medium and high exposure degree to mass information sources. The findings showed that the independent variable: agriculture knowledge, education level and age were explained about 43.43 percent of variability of level of exposure of individual information source. While educational level, Age and urban contact can explain about 32.5 percent of variability of level, of exposure of group information sources. But farmers attitude toward agriculture work and agriculture knowledge can explain nearly72.68 percent of variability of exposure level of mass information sources.